Flubendazole Elicits Antitumor Effects by Inhibiting STAT3 and Activating Autophagy in Non-small Cell Lung Cancer - Xie, Xiaona; Cai, Xueding; Tang, Yemeng; Jiang, Chunhui; Zhou, Feng; Yang, Lehe; Liu, Zhiguo; Wang, Liangxing; Zhao, Haiyang; Zhao, Chengguang; Huang, Xiaoying (Frontiers in Cell and Developmental Biology, 2021)
Non-small cell lung carcinoma (NSCLC) is a major main neoplastic disease with high mortality worldwide; however, effective treatment of this disease remains a challenge. Flubendazole, a traditional anthelmintic drug, possesses potent antitumor properties; however, the detailed molecular mechanism of flubendazole activity in NSCLC needs to be further explored. In the present study, flubendazole was found to exhibit valid antitumor activity in vitro as well as in vivo. Flubendazole blocked phosphorylation of STAT3 in a dose- and time-dependent manner and regulated the transcription of STAT3 target genes encoding apoptotic proteins. Further, flubendazole inhibited STAT3 activation by inhibiting its phosphorylation and nuclear localization induced by interleukin-6(IL-6). Notably, the autophagic flux of NSCLC cell lines were increased after flubendazole treatment. Furthermore, flubendazole down-regulated the expression of BCL2, P62, and phosphorylated-mTOR, but it upregulated LC3-I/II and Beclin-1 expression, which are the main genes associated with autophagy. Collectively, these data contribute to elucidate the efficacy of flubendazole as an anti-cancer drug, demonstrating flubendazole as a potential therapeutic agent via its suppression of STAT3 activity and the activation of autophagy in NSCLC.